Utilizing Wordwall.Net on the Improvement of Students’ Vocabulary Mastery: An ICT-Based Lesson - Wandari, Titin; Unsiah, Frida; Sahar, Rafidah (JOLLT Journal of Languages and Language Teaching, 2024)
The utilization of Information and Communication Technology (ICT) holds an important role in language learning, as it stimulates students’ enthusiasm for studying, encourages lifelong learning, enhances critical thinking skills, grants learners more autonomy, confidence, and motivation. In the EFL classroom, vocabulary mastery is one of the most important yet difficult language components especially for young learners to master. This study aimed to examine how vocabulary mastery of 7th grade students in one of public junior high schools in east Java, Indonesia were affected by ICT-based learning through wordwall.net. The study employed a one-group pre-test-post-test experimental design, with the numbers of 32 students. The participants were chosen through the purposive sampling technique. Pre-test and post-test were used to measure a student's vocabulary mastery before and after the treatment using wordwall.net. SPSS 21.0 was used for data analysis to find out whether the students’ vocabulary mastery get improved or not. The findings indicated that after using wordwall.net as the ICT based learning media, students' vocabulary mastery significantly improved. The improvement can be proven through the average pre-test score of 57.03 to the average post-test score of 77.34. In terms of the implementation, the usage of appropriate learning media, and student enthusiasm during the learning process are the reasons for the improvement of their vocabulary mastery.